Pengaruh Virtual Museum Di Era Covid-19 Terhadap Kunjungan Di Museum Multatuli Rangkasbitung - Fitra Riyanto; Emma Rochima (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
The Covid-19 pandemic has caused a multidimensional slump, including for the tourism industry. One strategy that can be used to keep increasing tourist visits is to take advantage of advances in digital technology. The virtual museum created by the Multatuli Museum can be a solution in accessing museums during the pandemic and increasing the number of visits during the COVID-19 pandemic and playing a role in introducing and promoting museums to the wider community. The purpose of this study was to measure how the public evaluates the virtual museum, to measure how much people are interested in visiting, and to measure how much influence the virtual museum has on interest in visiting the Multatuli Rangkasbitung Museum. The research was conducted using a qualitative method with a descriptive approach. The data were obtained from interviews, field observations, photo documentation of activities and literature studies. The results of the study show that the pandemic has made the Multatuli Museum manager carry out digital transformations in their public services. The use of virtual museums as a new medium is considered effective in increasing visiting interest. This study recommends the involvement of the parties that oversee the Multatuli Museum, namely the Education and Culture Office of Lebak Regency to provide real attention and assistance for the development of the virtual museum so that its benefits and objectives can continue to the wider community.